2022
DOI: 10.3390/nu14142926
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Adipose Tissue: A Novel Potential Imaging Marker of Comorbidities Caused by Chronic Inflammation

Abstract: The observation of correlations between obesity and chronic metabolic and cardiovascular diseases has led to the emergence of strong interests in “adipocyte biology”, in particular in relation to a specific visceral adipose tissue that is the epicardial adipose tissue (EAT) and its pro-inflammatory role. In recent years, different imaging techniques frequently used in daily clinical practice have tried to obtain an EAT quantification. We provide a useful update on comorbidities related to chronic inflammation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 130 publications
0
6
0
Order By: Relevance
“…Epicardial adipose tissue modulates the secretion of adipokines, molecules with an active role in the development of atherosclerosis [ 7 , 31 , 32 ]. In our study, we did not find statistically significant correlations between serum adipokine levels and epicardial adipose tissue thickness, but we attribute this result to the analysis of a small group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epicardial adipose tissue modulates the secretion of adipokines, molecules with an active role in the development of atherosclerosis [ 7 , 31 , 32 ]. In our study, we did not find statistically significant correlations between serum adipokine levels and epicardial adipose tissue thickness, but we attribute this result to the analysis of a small group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of imaging diagnostic methods and the dosage of molecules with a predictive role on the risk of an acute cardiovascular event are useful tools in clinical practice and research alike, and the evidence of correlations between them opens new research directions [ 7 ]. The connection between arterial stiffness and obesity has been highlighted in multiple clinical studies in the literature.…”
Section: The Role Of Imaging Methods In Cardiovascular Risk Assessmentmentioning
confidence: 99%
“…But there is also increasing evidence that the link between obesity and inflammation plays a major role in metabolic and cardiovascular diseases [ 51 53 ]. For instance, in a review paper Tarsitano et al discussed the specific relation between epicardial adipose tissue and its pro-inflammatory role in several cardiovascular diseases [ 54 ]. It has moreover been reported, that specific cardio-protective agents like Phosphodiesterase-5 inhibitors can positively affect the course of the diseases by modifying underlying inflammatory processes [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…EAT is unevenly distributed around the heart, with a higher concentration in the atrioventricular and ventricular grooves. 9 In some previous studies, computed tomography (CT) has been used to visualize EAT and evaluate its distribution. 10 , 11 Previous studies only suggested that the volume of EAT around the right ventricle may have a higher correlation with the frequency of PVCs.…”
Section: Introductionmentioning
confidence: 99%